Comparison of Postoperative Bleeding in Total Hip and Knee Arthroplasty Patients Receiving Rivaroxaban, Enoxaparin, or Aspirin for Thromboprophylaxis - Lindquist, Desirae E. (Clin Appl Thromb Hemost, 2018)
BACKGROUND: Guidelines recommend the use of multiple pharmacologic agents and/or mechanical compressive devices for prevention of venous thromboembolism, but preference for any specific agent is no longer given in regard to safety or efficacy. OBJECTIVE: To compare postoperative bleeding rates in patients receiving enoxaparin, rivaroxaban, or aspirin for thromboprophylaxis after undergoing elective total hip arthroplasty or total knee arthroplasty. METHODS: This retrospective cohort analysis evaluated patients who received thromboprophylaxis with either enoxaparin, rivaroxaban, or aspirin. All data were collected from the electronic medical record. The primary outcome was any postoperative bleeding. RESULTS: A total of 1244 patients were included with 366 in the aspirin, 438 in the enoxaparin, and 440 in the rivaroxaban arms. Those who received aspirin or enoxaparin were less likely to experience any bleeding compared to those patients who received rivaroxaban (P < .05). There was also a lower rate of major bleeding in these groups, but the differences were not significant. CONCLUSIONS: Aspirin and enoxaparin conferred similar bleeding risks, and both exhibited less bleeding than patients who received rivaroxaban.